Gastric emptying of liquid in children suffering from acute rotaviral gastroenteritis. Issue 1 (January 1992) - Bardhan, P K; Salam, M A; Molla, A M
Abstract : Nausea and vomiting commonly occur in children suffering from rotaviral diarrhoea. Gastric emptying was studied in 10 children (age six to 12 months) suffering from acute diarrhoea caused by rotavirus using a dye dilution double sampling technique. The test meal was 5% dextrose in water and this test was repeated 12 weeks after recovery. The median (range) of the percentages of the liquid meal remaining in the stomach at 5, 10, 20, 40, and 60 minutes after instillation of the meal were 82 (79-90), 70 (61-86), 51 (38-76), 26 (14-53), and 13 (2-35) respectively in the acute stage, whereas after the recovery period the values were 76 (70-79), 58 (49-63), 33 (24-40), 11 (2-26), and 3 (0-7). The differences were statistically significant. The half time of gastric emptying (t1/2) was 19.5 (14-30) minutes in acute stage, and 13.1 (10-15) minutes during follow up (p less than 0.01). Rotaviral gastroenteritis is accompanied by abnormal gastric motor function, as manifested by delayed emptying of a liquid meal.